2017
DOI: 10.1007/s00011-017-1049-z
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Fas/FasL pathway in the murine model of atopic dermatitis

Abstract: Objective and designThe aim of this study was to elucidate the role of apoptosis mediated through Fas/FasL pathway using the mouse model of atopic dermatitis (AD).Materials and treatment AD was induced by epicutaneous application of ovalbumin (OVA) in wild-type C57BL/6, B6. MRL-Faslpr/J (Fas−) and B6Smn.C3-Faslgld/J (FasL−) mouse strains.MethodsSkin samples were subjected to staining for Fas/FasL expression, M30 epitope and assessment of inflammatory response via immunohistochemical staining. Cytokine and chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The cell death machinery is activated by various apoptotic signals via the membrane (extrinsic) pathway. These apoptotic pathways are well studied in T cells, macrophages, and eosinophils, [20][21][22][23][24] like the pathway in which FasL activates Fas as a surface death receptor. One of the essential tools for the immune system to maintain immune homeostasis and to set up tolerance is to regulate cellular survival and death.…”
Section: Discussionmentioning
confidence: 99%
“…The cell death machinery is activated by various apoptotic signals via the membrane (extrinsic) pathway. These apoptotic pathways are well studied in T cells, macrophages, and eosinophils, [20][21][22][23][24] like the pathway in which FasL activates Fas as a surface death receptor. One of the essential tools for the immune system to maintain immune homeostasis and to set up tolerance is to regulate cellular survival and death.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the PI3K/AKT signaling pathway is one of the major Src-activating pathways and may block the FAS-associated death domain protein to inhibit cellular apoptosis [ 24 , 25 ]. Thus, it is likely that IL-17 exerts its function through the FAS and FASL signaling pathways [ 26 , 27 ]. To date, little is known about the roles of IL-17 in LC, and the regulation of IL-17 in LC has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors play important role in the pathogenesis of AD which involve genetic, environmental, skin barrier, psychological and immunological factors. In various studies, Fas/FasL mediated keratinocyte apoptosis was demonstrated to be an important component of eczema and spongiosis in AD patients[ 1 ]. Epidermal keratinocytes express Fas and FasL proteins in low amounts [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal expression of lytically active FasL was found in inflammatory skin diseases such as toxic epidermal necrolysis, atopic dermatitis and allergic contact dermatitis [ 3 ]. As described in detail previously [ 1 ], scientific evidence indicates that Fas/FasL death receptors activate inflammatory or proliferative signaling via NF-κB or MAP kinase pathway [ 4 ]. MAPK pathway consists of three major components: proline-directed serine/threonine kinase known as the extracellular signal-regulated kinase (ERK), p38 MAPK and c-Jun NH 2 -terminal kinase (JNK).…”
Section: Introductionmentioning
confidence: 99%